ANALISIS KESALAHAN BERDASARKAN NEWMAN ERROR ANALYSIS TERHADAP MATERI PELUANG KEJADIAN MAJEMUK DITINJAU DARI GENDER DAN SELF CONFIDENCE PADA SISWA KELAS XII SMK DI BANDUNG BARAT - Deajeng Putri Salamah (IKIP Siliwangi, 2020)
This study attempts to analyze their students on a compound the occurrence of matter newman. In terms of gender and the level of confidence. The study is done at student of class XII one vocational schools in west Bandung. By taking sample 5 male students and 5 female students.The methods used are qualitative descriptive with an instrument the written test , the survey, and an interview. A written test given 4 to word problems in one because there are two questions. The results, female students more confidence than male students. For female students are experiencing a mistake at the transformation while male students is starting to understand the problems at the mistake.